Piano Teaching for Preschool Education in Chinese Music University - Yanyu , Lin; Srisombut, Rujee (Journal of Roi Kaensarn Academi, 2024)
The article "Piano Teaching for Preschool Education in Chinese Music University" explores the current state, challenges, and methodologies of piano instruction within preschool education programs at Chinese music universities. The study examines the importance of piano teaching in developing the comprehensive musical and practical skills required by future preschool educators. Topics covered include curriculum design, music theory, performance techniques, improvisational accompaniment, and innovative teaching methods. Additionally, the paper highlights the role of piano education in fostering aesthetic appreciation and emotional development in preschool students. While addressing common issues such as varying student proficiencies and the integration of modern educational approaches, the article emphasizes the need for continuous reform and improvement in piano instruction. It argues for a more student-centered, practice-oriented, and diversified teaching framework to better prepare preschool educators for the evolving demands of early childhood music education in China.